Adherence to exercise after an acute coronary syndrome: a 6-month randomized controlled trial - Saarikoski, Essi O.; Roiha, Elina T. M.; Kiviniemi, Antti M.; Cerdán-De-las-Heras, Jose; Perkiömäki, Juha; Kaikkonen, Kari S.; Tulppo, Mikko P. (Frontiers in Physiology, 2024)
Introduction: Exercise training with well-known health benefits is a key element in the self-management of coronary artery disease (CAD). Although current guidelines for patients with CAD recommend daily exercise training, most of the patients do not follow the guidelines. We tested the hypothesis that an exercise training program guided by novel technology used at home will improve adherence to exercise training. Methods: One to three weeks after percutaneous coronary intervention (PCI), acute coronary syndrome patients (n=50) were randomized into traditional (age 65±8 years) and novel technology guided (age 60±8 years) exercise rehabilitation groups. Novel technology included a tablet computer with a Virtual Autonomous Physiotherapy Agent (VAPA group) for every patient at home; it was used to guide exercise training time, volume, and intensity. Traditional rehabilitation was performed by exercise training prescriptions, phone calls and diaries (CONTROL group). The duration of the rehabilitation program was six months for both groups. Exercise capacity and 24-h heart rate variability were measured at baseline and at the end of the program. Adherence to exercise was measured over six months as percentage of realized training. Results: None of the patients dropped out from the VAPA group while three dropped out from the CONTROL group. Adherence to exercise was higher in the VAPA group than in the CONTROL group in resistance training (141±56 % vs. 50±20 %, p<0.0001) and there were no differences in aerobic training (144±45 % vs. 119±65 %, p=0.22). Exercise capacity increased in both groups (time p<0.001, time x group interaction p=ns). High-frequency power of R-R intervals (lnHF) increased in the VAPA group but remained unchanged in the CONTROL group (natural logarithm of lnHF power from 5.5±0.7 to 5.8±0.9 ms2 and from 5.3±0.8 to 5.2±0.7 ms2, respectively, time x group interaction p=0.014). Conclusion: Compared with the use of traditional methods, the use of novel technology at home results in better adherence to exercise, particularly in resistance training, in acute coronary syndrome patients. Secondly, the VAPA group showed improved cardiac vagal regulation, documented by increased vagally mediated R-R interval fluctuation, compared with the traditional training group (ClinicalTrials.gov identifier: NCT03704025).